Continental Drift : Europe Approaching the Millenium. 10 Photographic Commissions. - Sand, Michael L.; McNeill, Anne (Munich : Prestel Verlag, 1998)
Lafontaine, Marie-Jo ; Bhimji, Zarina ; Parr, Martin ; Greene, Stanley ; Puranen, Jorma ; Fontcuberta, Joan ; Gregory, Joy ; Piper, Keith ; Myskja, Tone ; Waliczky, Tamás
This book as been published in conjunction with the simultanious openings in April 1998 of 10x98: the European Commissions in ten galleries across Yorkshire, England.
kunstcatalogus